OPTIMALISASI PEMBUATAN MIE BASAH DENGAN PENAMBAHAN TEPUNG DAUN KELOR (Moringa oleifara) - zakaria zakaria; suriani Rauf (Jurusan Gizi Poltekkes Kemenkes Makassar, 2017)
Background : Moringa leaf is a food of vegetables group whose utilization is still low, even though this plant has nutritional content that almost meets the nutritional needs of humans and is useful as a nutritional improvement. Objective: This study aims to determine the physical characteristics, acceptability, and chemical composition (protein and water) of wet noodles with the addition of moringa flour.Method: This research type is laboratory research with randomized block design, treatment with addition of 0%, 3%, 6%, 9% and 12% moringa flour. Implemented in Food Technology and Nutrition Laboratory of Makassar Health Polytechnic and Health Laboratory of Makassar. Parameter analysis is physical characteristics (rendemen, elasticity and brightness), panelist acceptance and chemical characteristics (water and protein content).Results: Physically wet noodles with the addition of Moringa leaf powder has randemen average above 95%, lower than the elasticity of the wet noodles without addition of moringa leaf powder. The color of wet noodles produced is getting green along with the increasing amount of addition of moringa flour. In general, panelists receive from the texture and taste aspects. Addition of maize flour 6-12% panalis stated rather like. Wet noodles with the addition of moringa leaves flour containing water averaged 36.7%, wet noodle protein content without the addition of moringa flour by 6.39%, 3% and 9% additions respectively 6.88% and 7.44% .Conclusion: Wet noodles with the addition of moringa flour has an average rendemen above 95%, greenness is bright, moderate elastitas. In general, panelists receive wet noodles on the addition of 3% moringa flour and slightly accept at 6-12%. Protein levels increased due to the addition of moringa flour.Keywords: Wet noodles, moringa flour